Analisis Pelaksanaan Pembelajaran Bahasa Inggris Kelas 3 di SDN Junrejo 2 - Ranti Dwi Kisowo; Endang Poerwanti; Belinda Dewi Regina (Advances In Education Journal, 2025)
English plays a vital role as a global means of communication and access to knowledge and future opportunities. However, preliminary findings at SDN Junrejo 2 showed that third-grade students still have limited vocabulary, face pronunciation difficulties, and show low learning motivation. This study aimed to describe the implementation of English learning in terms of planning, implementation, evaluation, challenges, and improvement efforts. A descriptive qualitative method was used, involving interviews, observations, and documentation with the English teacher, students, and principal. The results revealed that English learning had been conducted based on the Merdeka Curriculum using a direct instruction model. Challenges included students’ difficulty in concentration and pronunciation, as well as limited learning media and digital facilities. To overcome these, the school and teacher improved facilities, participated in training, implemented an English Day program, and used simple media with the drilling method.